Comparison of the Effectiveness of Two Different Vaccination Regimes for Avian Influenza H9N2 in Broiler Chicken - Talat, Shaimaa (Animals (Basel), 2020)
SIMPLE SUMMARY: The low pathogenic avian influenza H9N2 virus has been associated with severe economic losses in broiler chicken flocks. Problems associated with its control strategy are potential early infection and level of immune response that may be high in one-day-old chicks due to maternally derived antibodies. Herein, two vaccination regimes were evaluated in commercial broilers kept under either field or laboratory conditions. Two different vaccine types and concentrations were used, and the results highlighted a significantly higher protection against early infection when a homologous vaccine of high antigenic mass was applied at 7 days of life. Shedding was significantly reduced in this regime. ABSTRACT: Low pathogenic avian influenza virus is one of the major threats that has been affecting the poultry industry in the Middle East region for decades. Attempts to eradicate this disease have failed. Currently, there are commercial vaccines that are either imported or produced locally from recently circulating isolates of H9N2 in Egypt and Middle Eastern countries. This present work focused on comparing the effectiveness of two vaccines belonging to these categories in Egypt. Two commercial broiler flocks (Cobb-500 Broiler) with maternally derived immunity (MDA) against H9N2 virus were employed and placed under normal commercial field conditions or laboratory conditions. Immunity was evaluated on the basis of detectable humoral antibodies against influenza H9N2 virus, and challenge was conducted at 28 days of life using a recent wild H9N2 virus. The results showed that vaccination on the 7th day of life provided significantly higher immune response in both vaccine types, with significantly lower virus shedding compared to vaccination at day 1 of life, regardless of field or laboratory conditions. In addition, the vaccine produced from a recent local H9N2 isolate (MEFLUVAC-H9-16) provided a significantly higher humoral immune response under both field and laboratory conditions, as measured by serology and virus shedding (number of shedders and amount of shedding virus), being significantly lower following challenge on the 28th day of life, contrary to the imported H9 vaccine. In conclusion, use of H9N2 vaccine at 7 days of life provided a significantly higher protection than vaccination at day 1 of life in birds with MDA, suggesting vaccination regimes between 5–8-days of life for broiler chicks with MDA. Moreover, use of a vaccine prepared from a recently circulating H9N2 virus showed significantly higher protection and was more suitable for birds in the Middle East.